2019
DOI: 10.2147/bctt.s210788
|View full text |Cite
|
Sign up to set email alerts
|

<p>Positive margins (R1) risk factors in breast cancer conservative surgery</p>

Abstract: Background The primary goal in conservative breast cancer surgery is the complete excision of the tumor, but at the same time attempting to obtain a satisfactory postoperative esthetic result. The notion of “No Ink on Tumor” that indicates exclusively the presence of tumor cells on the inked surface of the surgical specimen is now the gold standard; however, the problem of the free margin is still a fundamental topic of debate that has not yet found a definitive solution. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 22 publications
(18 reference statements)
0
18
1
2
Order By: Relevance
“…The primary aim in BCS is to achieve a negative surgical margin while still preserving the aesthetically appealing breast. Adequate surgical margins have shown to decrease the incidence of local recurrence of the primary tumor [6][7][8][9][10]. To ensure negative margins, many techniques are suggested to assess the surgical margins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary aim in BCS is to achieve a negative surgical margin while still preserving the aesthetically appealing breast. Adequate surgical margins have shown to decrease the incidence of local recurrence of the primary tumor [6][7][8][9][10]. To ensure negative margins, many techniques are suggested to assess the surgical margins.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that in various treatment strategies (BCS alone, BCS with radiation therapy, or mastectomy), negative margin status strongly correlated with long-term disease-free survival. Positive margin has a negative effect on local recurrence and disease-free and overall survival of the patient [9,10]. To minimize the current reported high re-excision rates, intraoperative assessment of margins has become increasingly desired.…”
Section: Introductionmentioning
confidence: 99%
“…Radical resection is the main treatment for this disease. [ 24 ] The patient in this case underwent ipsilateral axillary lymph nodes clearance after extensive resection of the tumor. The margin of the lesion and the status of metastasis in axillary lymph nodes were determined by rapid frozen pathological examinations during the operation, to diminish the operational region as much as possible while completely removing the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-related death rates were estimated based on the PREDICT prognostication model [ 34 ]. The probability of nodal disease and R0 resection rates were extracted from the literature [ 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%